Penggunaan Internet dan Peluang Berwirausaha di Indonesia - Siburian, Nelsi Agustina; Nawawi, Zuhrinal M. (ManBiz: Journal of Management and Business, 2023)
Currently, the internet has become a necessity in social and economic life that provides convenience in communication and social interaction. In addition, the presence of the internet supported by advances in digital technology is expected to provide business opportunities. Internet access has become easier with the increasing use of mobile phones/handphones. This study aims to see the effect of internet use on entrepreneurial opportunities in Indonesia through descriptive analysis methods and binary logistic regression. This research uses data from the 2019 National Socio-Economic Survey. Entrepreneurs in this study are limited to individuals who try to be assisted by permanent workers or paid workers in the age range of 25 to 44 years. Of the 348,735 samples that were the analysis units, 7,108 were entrepreneurs or around 2.04 percent. This study found that individuals who use the internet have a higher chance of becoming entrepreneurs than individuals who do not use the internet and this finding is statistically significant. In addition, the level of education significantly influences individuals to become entrepreneurs, but individuals with higher education have a lower tendency to become entrepreneurs than those with high school education or below. Keywords: Internet, Binary Logistic Regression, Entrepreneurship